2004
DOI: 10.3406/rfeco.2004.1537
|View full text |Cite
|
Sign up to set email alerts
|

Recouvrement des coûts et demande de soins dans les PED

Abstract: [fre] Boubou Cissé Stéphane Luchini Jean-Paul Moatti Recouvrement des coûts et demande de soins dans les PED Suite à la crise financière qui a durement frappé les pays en développe- ment dès le début des années 1980, l'instauration du recouvrement des coûts d'accès aux soins (politique de tarification des prestations de services de santé) a été proposée à ces pays en 1985 puis en pratique exigée par la Banque mondiale à partir de 1987. Depuis lors, il y a eu de nombreuses controverses autour de l'impact de œs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Moreover, the level of education of the household head influences the expected health status of household members and therefore the use of formal health centers. Our results corroborate those from studies of households in sub-Saharan Africa, such as those of Eme Ichoku and Leibbrandt in Nigeria [ 52 ], Muriithi in Kenya [ 49 ], and Cissé et al [ 53 ] in the Ivory Coast. These results are, however, in contradiction to those of Gertler and Van der Gaag [ 54 ], who showed that the level of education of the head of household had no statistically significant relation with the seeking of health care.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the level of education of the household head influences the expected health status of household members and therefore the use of formal health centers. Our results corroborate those from studies of households in sub-Saharan Africa, such as those of Eme Ichoku and Leibbrandt in Nigeria [ 52 ], Muriithi in Kenya [ 49 ], and Cissé et al [ 53 ] in the Ivory Coast. These results are, however, in contradiction to those of Gertler and Van der Gaag [ 54 ], who showed that the level of education of the head of household had no statistically significant relation with the seeking of health care.…”
Section: Discussionsupporting
confidence: 91%
“…As we saw above, these utilization levels, while often higher than before, were nevertheless very low, and remained low 20 years after the fact. A synthesis article showed that some pilot projects even asserted that quality improvements could offset the negative impact of introducing user fees [ 73 ]. In Cameroon, for example, user fees without any quality improvement had negative impacts on the use of services by the worst-off.…”
Section: Pilot Projects That Are Essential Yet Unused/unusablementioning
confidence: 99%
“…On the other hand, other studies then explained that the links between price, quality, and utilization are more complex than that, and that the different aspects of each of these dimensions can affect outcomes. Quality improvement does not automatically compensate for negative effects of higher prices on service utilization [ 73 ].…”
Section: Pilot Projects That Are Essential Yet Unused/unusablementioning
confidence: 99%
“…Most of the patients had some form of health care insurance coverage (81.5%), for the most part a governmental insurance scheme (>95%). More than half of respondents received the service free 4 The test is based on augmented regression including squares and cubics of the fitted values. The auxiliary augmented model is:…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Many governments responded by implementing stabilization and structural adjustment programs [3], proposed and subsequently demanded by international organizations, e.g., the World Bank [4] and the International Monetary Fund [5]. Hence, these states were obliged to restrict their social expenditures including health care budgets [6], with the risk of compromising the provision of good quality care.…”
Section: Introductionmentioning
confidence: 99%